2005
DOI: 10.1111/j.1439-0523.2005.01153.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of some surviving on‐farm Italian common bean (Phaseolus vulgaris L.) landraces

Abstract: This study was undertaken to estimate the level of variation among and within 33 local populations belonging to seven Italian common bean landraces, by analysing the polymorphism of seed storage proteins, simple sequence repeat (SSR) and amplified fragment length polymorphism (AFLP) molecular markers. The nutritional seed quality of the landraces studied was also investigated. Results showed that the landraces retain a considerable level of heterogeneity. Use of both biochemical and molecular approaches provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 31 publications
2
45
2
Order By: Relevance
“…According to Gepts and Bliss (1986), dry bean genotypes with 100-seed weights less than 25 g normally belong to the Mesoamerican group and those with weights near or above 33 g, would be from the Andean group. Lioi et al (2005), evaluating the genetic diversity of 33 dry bean populations with SSR and amplified fragment length polymorphism (AFLP) markers, observed that both types of markers grouped the genotypes into Andean and Mesoamerican centers of origin. Benchimol et al (2007), in a study of the genetic diversity of 20 dry bean genotypes, using SSR markers, observed that two large groups were formed, one containing the Andean-origin genotypes and the other the Mesoamerican-origin genotypes.…”
Section: Resultsmentioning
confidence: 99%
“…According to Gepts and Bliss (1986), dry bean genotypes with 100-seed weights less than 25 g normally belong to the Mesoamerican group and those with weights near or above 33 g, would be from the Andean group. Lioi et al (2005), evaluating the genetic diversity of 33 dry bean populations with SSR and amplified fragment length polymorphism (AFLP) markers, observed that both types of markers grouped the genotypes into Andean and Mesoamerican centers of origin. Benchimol et al (2007), in a study of the genetic diversity of 20 dry bean genotypes, using SSR markers, observed that two large groups were formed, one containing the Andean-origin genotypes and the other the Mesoamerican-origin genotypes.…”
Section: Resultsmentioning
confidence: 99%
“…These actions are generally necessary in order to pursue landrace valorization through quality marks or the inscription to the Register of Conservation Varieties [9]. In this work, we set out to describe with morphological traits and molecular markers three accessions belonging to the 'Badda' landrace, in comparison with several reference materials and with landraces showing morphological and/or geographical proximity.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, relatively few traditional types have been accepted into alternative variety protection systems. To counteract this phenomenon, owing to the interest raised by bean landraces both as a germplasm source for breeding programs and as an added-value produce to be valorized in local and niche markets, the characterization of the Italian treasure of bean local varieties has recently been undertaken by several authors [5,[7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The germplasm, preserved on farm by the Consorzio di Tutela dei Fagioli di Sarconi, has been extensively characterised for its biochemical and nutriceutical traits (Piergiovanni et al 2000;Lioi et al 2005;Dinelli et al 2006) but nothing is known about its response to diseases. As a matter of fact, the above varieties are plagued by the common bacterial blight (CBB), caused by Xanthomonas axonopodis pv.…”
Section: Introductionmentioning
confidence: 99%